Contribution of live fences to control the heat stress in dairy cows in the humid tropic of Costa Rica - Argeñal Vega, P.R. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- IICA, Turrialba (Costa Rica),2011